Pengaruh Aplikasi Biochar Jerami Padi dan Rhizobium terhadap Pertumbuhan dan Hasil Kedelai Hitam - Helen Puspa Juliasari; Titiek Islami; Anna Satyana Karyawati (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2024)
Black soybeans in Indonesia have high economic value due to their potential for processing into various products and their health benefits. The high utilization of black soybean is supported by its rich nutritional content, particularly the protein levels in its seeds. There is a gap between the demand for and availability of black soybeans in Indonesia. Effective measures are needed to increase black soybean yields. One approach is to enhance the efficiency of organic fertilizer use by applying rice straw biochar as a soil amendment and Rhizobium as a biofertilizer to improve the growth and yield of black soybeans. This study was conducted using a two-factor experimental design with doses of rice straw biochar (0, 10 t.ha-¹, and 15 t.ha-¹) and doses of Rhizobium (0, 5 g.kg-¹ seed, 10 g.kg-¹ seed, and 15 g.kg-¹ seed). An interaction was observed between the application of 10 t.ha-¹ of biochar and 5 g.kg-¹ of Rhizobium, which significantly affected the yield of black soybean, including the number of filled pods per plant, seed weight per plant, harvest yield per hectare, and total seed protein content.